2020
DOI: 10.1007/s12551-020-00761-x
|View full text |Cite
|
Sign up to set email alerts
|

The rich inner life of the cell nucleus: dynamic organization, active flows, and emergent rheology

Abstract: The cell nucleus stores the genetic material essential for life, and provides the environment for transcription, maintenance, and replication of the genome. Moreover, the nucleoplasm is filled with subnuclear bodies such as nucleoli that are responsible for other vital functions. Overall, the nucleus presents a highly heterogeneous and dynamic environment with diverse functionality. Here, we propose that its biophysical complexity can be organized around three inter-related and interactive facets: heterogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 121 publications
(183 reference statements)
4
23
0
1
Order By: Relevance
“…The requirement for nomination is that the young scientist be currently involved in biophysical research and be under 40 by the deadline of application. In 2020, the inaugural ‘Michèle Auger Award for Young Scientists’ Independent Research’ was conducted and this competition was won by Dr. Alexandra Zidovska, Assistant Professor at New York University (Hall 2020b ; Zidovska 2020 ). For the 2021 award, the journal received 15 nominations.…”
Section: Winner Of the Michèle Auger Award For Young Scientists’ Indementioning
confidence: 99%
“…The requirement for nomination is that the young scientist be currently involved in biophysical research and be under 40 by the deadline of application. In 2020, the inaugural ‘Michèle Auger Award for Young Scientists’ Independent Research’ was conducted and this competition was won by Dr. Alexandra Zidovska, Assistant Professor at New York University (Hall 2020b ; Zidovska 2020 ). For the 2021 award, the journal received 15 nominations.…”
Section: Winner Of the Michèle Auger Award For Young Scientists’ Indementioning
confidence: 99%
“…For those interested in entering (or nominating another) additional details about the judging and selection of winners for the previous years' competitions can be found in the following references: Hall (2020bHall ( , 2020cHall ( , 2020d; Hall (2021bHall ( , 2021c. The 2020 winner's published review article can be found here (Zidovska 2020) with the 2021 winner's published review article set to appear in the upcoming Issue 4.…”
Section: A Well-written Commentarymentioning
confidence: 99%
“…The winner's published Review will carry a short foreword about the life of Professor Michèle Auger, along with her work associated with teaching and training the next generation of biophysical scientists. First run in 2020, the two previous winners were Assistant Professor AlexandraZidovska (2020) and Associate Professor Jorge Alegre-Cebollada (2021). Their public research details can be found below.…”
mentioning
confidence: 99%
“…A feature of this Issue was the invited review article by Dr. Alexandra Zidovska, the inaugural winner of the Michèle Auger award for young scientists’ independent research (Hall 2019a , b ; IUPAB 2018 ). In her award article Alexandra reviewed salient material within her thematic topic of cytosol rheology (Zidovska 2020 ). In addition, her article carried two short personal biographies of both herself and Michele Auger—the scientist and former Biophysical Reviews Editorial Board Member for whom the award acts as a perpetual memorial.…”
Section: Highlights Of 2020mentioning
confidence: 99%